Miracle Literacy Training (MLT) for Nonchaplain Clinicians - Penate, Edward; Hauser, Joshua; Holiona, Dana (Journal of pain and symptom management, 2025)
1. Evaluate the feasibility and effectiveness of a Miracle Literacy Training curriculum for non-chaplain clinicians. 2. Review recommendations for Miracle Literacy Training and explore possible future research opportunities. The authors developed an intervention, Miracle Literacy Training, to train non-chaplain clinicians to navigate complex conversations when patients and family members express hopes for miracles in situations involving complex medical decision-making. The training was based on a literature review, needs assessment, an interdisciplinary expert panel, and pilot testing. Feedback was elicited through a questionnaire and post-training individual and group interviews. There is increasing recognition of challenges associated with conversations when patients/family members express hopes for miracles in complex medical decision-making (1,2,3,4). To our knowledge, no standardized training models for this training exist, nor are there published evaluations of a specialized curriculum and its impact on clinical practice. The project aimed to evaluate the effectiveness of MLT for non-chaplain clinicians, particularly to 1) understand the clinician's spiritual care (SC) experiences and skills related to miracle literacy 2) identify impactful curricular elements for clinical practice. Between January 1 and December 31, 2023, nine medical students and two physician assistants rotating on the palliative care service participated in the curriculum, which involved three virtual one-hour sessions. The training was based on a literature review, needs assessment, an interdisciplinary expert panel, and pilot testing. A pre- and post-training questionnaire was administered. All participants were interviewed either individually or in small groups to study curricular effects. Chi-squared tests for differences assessed the statistical significance of quantitative data. Two researchers independently conducted a thematic analysis of qualitative post-training interview data. Results: Eleven participants took part in MLT. Each completed pre- and post-training questionnaires and engaged in a post-training interview. Statistically significant differences were observed in self-reported confidence in conducting generalist-level SC/communication tasks (e.g., responding and exploring) associated with MLT before and after training. Three core themes emerged from individual and group interviews: 1) Content and/or Competencies, 2) Educational Methods, and 3) Curricular Recommendations. This project demonstrates initial feasibility and effectiveness of MLT. The curriculum equipped MSs and PAs with the knowledge and skills to offer generalist-level SC, improving the clinicians' confidence to provide SC in complex clinical scenarios involving hopes for a miracle. It presents a promising approach for training clinicians in discussing hopes for a miracle with patients/families, warranting further investigation. 1. Bibler, T. M., Shinall, M. C. Jr., Stahl, D. Responding to Those Who Hope for a Miracle: Practices for Clinical Bioethicists. Am J Bioeth. 2018 May;18(5):40-51. doi: 10.1080/15265161.2018.1431702. PMID: 29697329. 2. Cain, C. L., Surbone, A., Elk, R., et al. Culture and Palliative Care: Preferences, Communication, Meaning, and Mutual Decision Making. J Pain Symptom Manage. 2018 May;55(5):1408-1419. doi: 10.1016/j.jpainsymman.2018.01.007. Epub 2018 Jan 31. PMID: 29366913. 3. Puchalski,C. and Hanzo, G. "There Is Going to Be a Miracle”—Decision-Making When Religious Beliefs and Medical Realities Conflict, Journal of Pain and Symptom Management, 2015 49(2):388. 4. Shinall, M. C. Jr., Stahl, D., Bibler, T. M. Addressing a Patient's Hope for a Miracle. J Pain Symptom Manage. 2018 Feb;55(2):535-539. doi: 10.1016/j.jpainsymman.2017.10.002. Epub 2017 Oct 10. PMID: 29030208; PMCID: PMC10182410.